2010
DOI: 10.1111/j.1476-5381.2010.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of CYP2D6 and CYP3A activities on the pharmacokinetics of immediate release oxycodone

Abstract: Background and purpose:There is high interindividual variability in the activity of drug-metabolizing enzymes catalysing the oxidation of oxycodone [cytochrome P450 (CYP) 2D6 and 3A], due to genetic polymorphisms and/or drug-drug interactions. The effects of CYP2D6 and/or CYP3A activity modulation on the pharmacokinetics of oxycodone remains poorly explored. Experimental approach: A randomized crossover double-blind placebo-controlled study was performed with 10 healthy volunteers genotyped for CYP2D6 [six ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
150
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(163 citation statements)
references
References 24 publications
9
150
2
2
Order By: Relevance
“…This was confirmed by the absence of significant difference in the C max between the two periods. Moreover, a shunt of a CYP2D6 substrate to metabolism via secondary weekly metabolic pathways such as CYP3A5, when CYP2D6 was deficient, was described in previous studies (Samer et al, 2010;Heiskanen et al, 1998). Thus, the metabolism of BCQB by other enzymes such as CYP3A4/5 and CYP2C19 could also lessen the exposure of BCQB after inhibition of CYP2D6 by paroxetine.…”
Section: Discussionmentioning
confidence: 78%
“…This was confirmed by the absence of significant difference in the C max between the two periods. Moreover, a shunt of a CYP2D6 substrate to metabolism via secondary weekly metabolic pathways such as CYP3A5, when CYP2D6 was deficient, was described in previous studies (Samer et al, 2010;Heiskanen et al, 1998). Thus, the metabolism of BCQB by other enzymes such as CYP3A4/5 and CYP2C19 could also lessen the exposure of BCQB after inhibition of CYP2D6 by paroxetine.…”
Section: Discussionmentioning
confidence: 78%
“…When one isoform is not available (due to inhibition, downregulation, or nonexpression) drugs may be shunted through alternative CYP enzymes resulting in alternative metabolites with varying affinity for the target receptor. Samer et al elegantly demonstrated this phenomenon by inhibiting CYP 3A4 and showing that oxycodone is then metabolized by CYP2D6 to a more potent metabolite [18]. Thus, characterization of the full spectrum of CYP metabolic capacity and understanding of the drug affinities for specific enzymes are necessary to predict the metabolite profile in an individual patient.…”
Section: Genomics Of Drug Metabolizing Enzymesmentioning
confidence: 99%
“…OXY displays analgesia through µ-and probably also κ-opioid receptors [50] and activation of GABA B receptors [51]. OXY is metabolized through the P-450 system, predominantly CYP3A4 to inactive noroxycodone, and to a less extent via CYP2D6 to oxymorphone that displays analgesic effect [52]. Morphine acts exclusively via activation of predominantly μ-opioid receptors and mostly undergoes glucuronidation; it is metabolized through CYP2D6 to a less extent [53].…”
Section: Research Wojciech Leppertmentioning
confidence: 99%